The strength model of self-control: Recent advances and implications for public health - Hagger, Martin; Chatzisarantis, Nikos (2013)
The strength model of self-control conceptualizes self-control as a resource that enables individuals to actively control impulses and urges, but is finite and, after a period of exertion, becomes depleted. In this chapter we discuss the main hypotheses of the strength model, review the current state of the research adopting the model including the recovery, conservation, and training hypotheses, identify the mechanisms that underpin the model including recent advances, summarize the contribution of the model to public health contexts, and provide details of the future research directions to advance the contribution the model makes to understanding self-control. We conclude that the model has provided a useful framework to understand self-control in numerous health-related contexts with training or practice on self-control offering considerable potential for interventions to promote health-related behavior. Future research should elucidate the mechanisms underpinning the effects of self-control resource depletion on behavior and identify the moderators of the effect.